Diseño y construcción de un tablero para realizar mediciones en corriente continua. - Conde Castillo, Gabriel Alexander (2013)
This practical work is aims to contribute to the improvement of academic activities through building a practice board for dc measurements, on the board through experimentation can check the theoretical knowledge studied in class as: Ohm's law and the different types of connections. In each session the student will observe and compare the data arising from theoretical calculations and actual data taken with the measuring instruments which are on the board. The design and selection of the various components have enabled experimentation effects carry circuits, obtaining adequate results to the expectations raised by this work which has become an educational instrument to teach dc measurements. The use of this equipment in teaching allows students to develop skills and abilities when making a practice, to analyze the behavior of the different ways of connecting the resistors and get electrical parameters that can be tested. Once experimentation carried into effect can be seen that the theoretical and measured data are closely related, with the theory and practice of great importance in the study of this subject. The need arises to recommend that before carrying out a practice students need to understand the scientific and academic work essential to make to be motivated learning within the student experience avoiding missteps in experimentation. It is necessary for the implementation of practices that arming students circuits according to the schematics, electrical calculations and measurements made in a sequence of logical steps in relation to practical guidance in order to avoid damage to the equipment.